PENGARUH CSR DAN PROFITABILITY TERHADAP FIRM VALUE DENGAN EARNINGS MANAGEMENT SEBAGAI PEMODERASI - Lisa Septiani, F.X Kurniawan Tjakrawala (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to determine the effect of CSR disclosure and profitability on Firm Value with Earnings Management as a moderating variable on manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. This study uses 65 samples of manufacturing companies that are determined by using purposive sampling. This research data was calculated with Microsoft Excel 2016 software and processed with Eviews 10. The results showed that CSR has a negative and not significant effect on Firm Value, Profitability has a negative and significant effect on Firm Value, Earnings Management has no significant effect in moderating the relationship of CSR to Firm Value, and Earnings Management has negative significant in moderating the relationship between Profitability and Firm Value.